Online customer engagement on instagram: An analysis of subscription video-on-demand services’ posts - Simões, Bárbara Gomes (2022)
Social media has become one of the most influential and important virtual platforms, both for users and businesses. Thus, there has been a growing necessity for insight into what works for each industry. That leads to this study’s main goal, which is to investigate the influence of social media posting of subscription video-on-demand services (Netflix Portugal, Disney Plus Portugal and HBO Portugal) on Portuguese customer engagement. Therefore, a literature review was conducted about customer engagement, social media post characteristics, eWOM comment valence and the relationship between SVoD services and social media. As a netnography, posts from Netflix Portugal, Disney Plus Portugal and HBO Portugal were collected, over the period of one month, for a total of 142 posts. Also, 3402 comments were analysed using VADER lexicon and sentiment analysis tool. The statistical analyses allowed to conclude that an image and emotional appeal increases the number of likes, the use of a carousel increases the number of likes and comments, while interactivity decreases the number of likes and comments. It is also possible to do a reliable prediction for the number of likes based on the use of a carousel, the interactivity and the post appeal, as well as for the number of comments based on the use of a carousel and interactivity. There was no statistically significant relation between the post characteristics and eWOM comment valence. Managers of SVoD brands can be guided by this research with regard to deciding which characteristics they should use when posting.